The recent development of interferometer prototype for Chinese gravitational wave detection pathfinder mission. (September 2018) - Luo, Ziren; Liu, Heshan; Jin, Gang
Highlights: Comparing to LISA pathfinder's design, we achieve the same performance by using less components. Comparing to LISA pathfinder's design, the components are parallel or perpendicular, easier for positioning and bonding. Comparing to LISA pathfinder's design, equal arm-length design, minimize the laser frequency noise for the interferometer. Comparing to our previous result, we studied the thermal drifting noise and improved it for a factor of 6. Comparing to our previous result, we optimized the electronics and the noise was improved for nearly 10 times. Abstract: A brief progress report is presented on the interferometer prototype of the Chinese gravitational wave detection pathfinder mission. After careful consideration of the temperature fluctuation induced noise and the electronic noise, the noise spectra density of the interferometer prototype reached 100 pm / Hz at 1 mHz and achieved 15 pm / Hz in high frequency region. However, in some frequency range from 3 mHz to 30 mHz, further improvement is still needed. Possible improvement is also discussed.